1990
DOI: 10.1063/1.345806
|View full text |Cite
|
Sign up to set email alerts
|

An experimental estimation of silicon interstitial diffusivity

Abstract: A relatively simple experimental method to estimate a diffusivity of silicon interstitials is described. In the low-temperature range between 460 and 500 °C, oxygen thermal donors are used as a monitor for silicon interstitials. The estimated diffusivity of silicon interstitials at oxygen-donor-formation temperatures is fitted to previously-published results from oxidation-enhanced and retarded-diffusion experiments at temperatures above 950 °C. In the temperature range between 460 and 1200 °C, the diffusivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…The low value was tentatively attributed to enhancements resulting from the irradiation procedure. Wijaranakula reported a large activation energy of 180 kJ/mol (1.86 eV), 48 based on experiments where oxygen donors were used to trace Si interstitial motion. Neither experimental study indicated the charge state of the Si i .…”
Section: Activation Energiesmentioning
confidence: 99%
“…The low value was tentatively attributed to enhancements resulting from the irradiation procedure. Wijaranakula reported a large activation energy of 180 kJ/mol (1.86 eV), 48 based on experiments where oxygen donors were used to trace Si interstitial motion. Neither experimental study indicated the charge state of the Si i .…”
Section: Activation Energiesmentioning
confidence: 99%
“…Measurements of the diffusion rate of defects in silicon have been reported in experiments. [8][9][10][11][12][13][14] Current experimental techniques cannot cleanly resolve the diffusion rates of more complex defect species, and due to the atomicscale size of point defects, defect diffusion pathways cannot be resolved at all. 15 Thus, numerical simulations provide a unique way to study the technologically important dynamics of point defects in silicon.…”
mentioning
confidence: 99%
“…The sample is MCZ3 subjected to annealing at 4500C for 24 h. TD concentrations are found to increase with depth as already reported [6,8,9]. TD depth profiles were fitted to the error function equation [8] TD(x)=TDS + (TDB -TDs)erf(x/2DTDt) ()…”
Section: Resultsmentioning
confidence: 99%
“…TD depth profiles were fitted to the error function equation [8] TD(x)=TDS + (TDB -TDs)erf(x/2DTDt) ()…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation